2015
DOI: 10.1088/0953-2048/29/1/014002
|View full text |Cite
|
Sign up to set email alerts
|

Field and temperature scaling of the critical current density in commercial REBCO coated conductors

Abstract: Scaling relations describing the electromagnetic behaviour of coated conductors (CCs) greatly simplify the design of REBCO-based devices. The performance of REBCO CCs is strongly influenced by fabrication route, conductor architecture and materials, and these parameters vary from one manufacturer to the others. In the present work we have examined the critical surface for the current density, Jc(T,B,), of coated conductors from six different manufacturers: American Superconductor Co. (US), Bruker HTS GmbH (Ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 33 publications
6
85
1
Order By: Relevance
“…Recently, it has been shown that the T dependence of J C of CCs from different manufacturers can be described over a broad range of temperatures and fields by an exponential law, J C ðT; BÞ ¼ J C ðT ¼ 0; BÞe ÀT=T Ã . Deviations from this behavior are observed at temperatures տ 50 K. 22 The exponential dependence of J C is connected with the presence of defects generating weak isotropic pinning, and T Ã is the characteristic pinning energy at these defects. 23,24 Other dominant pinning mechanisms can lead to different J C ðT; BÞ characteristics.…”
Section: Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, it has been shown that the T dependence of J C of CCs from different manufacturers can be described over a broad range of temperatures and fields by an exponential law, J C ðT; BÞ ¼ J C ðT ¼ 0; BÞe ÀT=T Ã . Deviations from this behavior are observed at temperatures տ 50 K. 22 The exponential dependence of J C is connected with the presence of defects generating weak isotropic pinning, and T Ã is the characteristic pinning energy at these defects. 23,24 Other dominant pinning mechanisms can lead to different J C ðT; BÞ characteristics.…”
Section: Tmentioning
confidence: 98%
“…25 The T Ã values associated with tapes from different manufacturers, for different orientations between the field and the tape surface, are reported in Ref. 22. From the expression for J C ðT; BÞ, one can easily deduce the following formula that relates T CS to parameters directly chosen by the magnet designer, namely, the operating conditions and the current margin…”
Section: Tmentioning
confidence: 99%
“…Due to sensitivity of used materials to the applied magnetic field: the critical current density (Jc) in case of superconductors [18] and the relative magnetic permeability in case of a ferromagnetic material, the cloaking effect was observed only for the small range of the applied field amplitudes. The optimal performance for the BSCCO-2212 insert and REBCO insert is observed by fields that are not the same.…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxy in the HTSC layer is obtained by using rolling‐assisted, bi‐axially textured substrates as tape, and via the buffer layers which can be ion beam assisted deposited or inclined substrate deposited (under an angle). Deposition of the YBCO layer is accomplished via metal‐organic inkjet printing, followed by thermal pyrolytic treatments . In 2016, impressive values for j c of up to 3.5 × 10 6 A cm −2 have been reached in the laboratories of some of the major industrial players.…”
Section: Superconducting Perovskitesmentioning
confidence: 99%